Spatiotemporal Variations in the Urban Heat Islands across the Coastal Cities in the Yangtze River Delta, China. Issue 5 (3rd September 2021) - Shi, Xiao; Xu, Yongming; Wang, Guojie; Liu, Yonghong; Wei, Xikun; Hu, Xue
Abstract: Over 70% of the cities in China are experiencing urbanization, and urban heat island intensity (UHII) evaluation studies have been widely performed. However, under the rapid economic development in China, few studies on surface urban heat island (SUHI) interannual variations have been conducted in coastal cities in the leading economic region of the Yangtze River Delta. In this study, the long-term summer daytime SUHI from 2001 to 2019 is studied based on the remotely sensed land surface temperature (LST) in 11 coastal cities in the Yangtze River Delta. The results show that notable SUHIs occur in the study area with high spatial heterogeneity, particularly in the central area, including Shanghai, Hangzhou, and Ningbo. The SUHI trends are not synchronous across the study area, with suburban areas revealing higher trends than city center areas. In addition, all 11 cities show an increasing trend of the urban heat proportion index (UHPI) over 19  years, which is more profound in Shanghai and Zhoushan but less profound in Lianyungang and Wenzhou. The strong correlation between the UHPI and artificial impervious coverage indicates that artificial impervious coverage plays an important role in determining the spatial and temporal distributions of the summer daytime SUHI in the 11 coastal cities, which are especially notable in Ningbo and Taizhou.